1995
DOI: 10.1177/000992289503400205
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury in Youth

Abstract: To identify special characteristics of the pediatric spinal cord-injured (SCI) population, we analyzed a database of 1,770 traumatic SCI patients; 88 (5%) fell into the two pediatric subgroups: 0-12 years (n = 26) and 13-15 years (n = 62) at time of injury. Differences between age groups were identified with regard to demographics, neurologic characteristics, associated injuries and complications, and management. Mode level of bony injury was C2 in preteens, C4 in teens, and C4-C5 in adults. Scoliosis develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…1,13 The era of initial treatment and the long time scale of retrospective selection may have in¯uenced some of the characteristics, and largely accounts for the response rate (42%) from those we attempted to contact. The proportion of subjects with tetraplegia and incomplete lesions is less than in some recent reports 1,14,15 but this study shares with many previous publications on childhood onset SCI the potential confounding association of younger age at injury with paraplegia and paraplegia with complete lesions. 16±18 Scoliosis (a) Consistent with previous clinical and radiological assessments, this study found that more severe scoliosis related to younger age at onset of paralysis.…”
Section: Study Groupsupporting
confidence: 76%
“…1,13 The era of initial treatment and the long time scale of retrospective selection may have in¯uenced some of the characteristics, and largely accounts for the response rate (42%) from those we attempted to contact. The proportion of subjects with tetraplegia and incomplete lesions is less than in some recent reports 1,14,15 but this study shares with many previous publications on childhood onset SCI the potential confounding association of younger age at injury with paraplegia and paraplegia with complete lesions. 16±18 Scoliosis (a) Consistent with previous clinical and radiological assessments, this study found that more severe scoliosis related to younger age at onset of paralysis.…”
Section: Study Groupsupporting
confidence: 76%
“…15 Boys dominate the injuries among children, which was higher than previous studies. [16][17][18] In this study, the only girl in the child population was injured as a pedestrian, whereas the cause of injury was more diverse among the boys.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions with complete sensorimotor restitution were also included, as defined by ASIA Impairment Scale grade E, 17 if there was documented evidence of symptoms and signs of SCI with a duration of at least 2 weeks postinjury. 18 Sources Three types of sources were used: (1) Nationwide Inclusion criteria and exclusion criteria (Table 1) The procedure of finding the children and the verification of the diagnosis is fully described in our paper Pediatric Spinal Cord Injury in Sweden. How to identify a cohort of rare events.…”
Section: Definitionmentioning
confidence: 99%
“…1 During the last decade, especially in the USA, childhood SCI have received increasing coverage in the literature. This subgroup has special needs because of the ongoing physical, intellectual, psychological and social development that characterizes the child and teenager.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation